2020
DOI: 10.1021/acs.nanolett.0c01659
|View full text |Cite
|
Sign up to set email alerts
|

Single Nanoparticle Chiroptics in a Liquid: Optical Activity in Hyper-Rayleigh Scattering from Au Helicoids

Abstract: Linear optical methods of determining the chirality of organic and inorganic materials have relied on weak chiral optical (chiroptical) effects. Nonlinear chiroptical characterization holds the potential of much greater sensitivity and smaller interaction volumes. However, suitable materials on which to perform measurements have been lacking for decades. Here, we present the first nonlinear chiroptical characterization of crystallographic chirality in gold helicoids (≈150 nm size) and core/shell helicoids with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 32 publications
0
44
0
Order By: Relevance
“…Such behaviour holds significant promise in the development of new spectroscopic methods to interrogate chiral substances that exhibit a low dissymmetry. [1][2][3][4] Whether such approaches have broader impact in applications exploiting light-matter interactions remains to be seen.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such behaviour holds significant promise in the development of new spectroscopic methods to interrogate chiral substances that exhibit a low dissymmetry. [1][2][3][4] Whether such approaches have broader impact in applications exploiting light-matter interactions remains to be seen.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…The interaction of CP light with chiral molecules (and vice versa) underpins a range of spectroscopies already routinely used to interrogate chiral substrates -(electronic/vibrational) circular dichroism (ECD, VCD), optical rotation/rotatory dispersion (ORD), Raman optical activity (ROA) -and continues to be of interest in cutting edge developments in the measurement sciences. [1][2][3][4] The aim to use CP light in asymmetric synthesis is a historically important example. As early as the 19 th century, it was suggested that CP light could be used for the selective production of an enantioenriched substance, and CP lightdependent photochemical reactions remain a candidate for the origin of the homochirality of life.…”
Section: Introductionmentioning
confidence: 99%
“…[59] The illumination volume in a sample cell (dispersing Au@SiO 2 core@shell helicoids III, with a size of ≈150 nm) was estimated to be ≈30 µm 3 , so that the HRS OA signals were collected from 0.05-0.13 of individual (or sub-single) helicoids. [60] The HRS has a wavelength of ≈375 nm under the 720-nm excitation, well above any other multiphoton emission; and the HRS intensities ( RCP…”
Section: Sub-single-particle Hyper-rayleigh Scattering Optical Activitymentioning
confidence: 99%
“…[ 14 ] In addition, the photothermal dichroism has also been realized by depositing plasmonic chiral NPs on a thin AlGaN: Er 3+ film, which exhibits both optical and photothermal chirality due to the circular differential absorption. [ 15 ] However, the physical mechanism for the GNH‐enabled chiroptical modulation remains unclear, though the single‐particle chiral scatterometry [ 16 ] and hyper‐Rayleigh scattering [ 17 ] of the GNHs in solution have been investigated. Further study on the chiral PL properties of the GNHs is expected to elucidate the relationship between excitation/emission circular polarization and the handedness of chiral emitters in many chirality‐related modulation and PL processes.…”
Section: Introductionmentioning
confidence: 99%